Carlos arquitecto Jiménez - Fernandez-Galiano, Luis (2001)
Sobre la obra del arquitecto costaricense: sus antecedentes, referentes proyectuales y su carrera en EEUU.
Keywords: JIMENEZ, CARLOS; ARQUITECTURA; CRITICA; COSTA RICA; ESTADOS UNIDOS